ECG-Based Indices to Characterize Persistent Atrial Fibrillation Before and During Stepwise Catheter Ablation - McCann, Anna; Vesin, Jean-Marc; Pruvot, Etienne; Roten, Laurent; Sticherling, Christian; Luca, Adrian (Frontiers in Physiology, 2021)
Background: Consistently successful patient outcomes following catheter ablation (CA) for treatment of persistent atrial fibrillation (pers-AF) remain elusive. We propose an electrocardiogram (ECG) analysis designed to (1) refine selection of patients most likely to benefit from ablation, and (2) examine the temporal evolution of AF organization indices that could act as clinical indicators of ongoing ablation effectiveness and completeness. Method: Twelve-lead ECG was continuously recorded in 40 patients (61 $±$ 8 years) during stepwise CA (step-CA) procedures for treatment of pers-AF (sustained duration 19 $±$ 11 months). Following standard pre-processing, ECG signals were divided into 10 s epochs and labeled according to their temporal placement: pre-PVI (baseline), dur-PVI (during pulmonary vein isolation), and post-PVI (during complex-fractionated atrial electrograms and linear ablation). Instantaneous frequency (IF) and adaptive organization index (AOI) measures were calculated and analyzed during each of the three temporal steps. Temporal evolution of these measures was assessed using a statistical test for mean value transitions, as an indicator of changes in AF organization. Results were then compared both between patients grouped according to CA outcome, and within the same patient group during the three different temporal steps. Results: Stepwise CA patient outcomes were as follows: (1) left-atrium (LA) terminated, not recurring (LTN, n=8), (2) LA terminated, recurring (LTR, n=20), and (3) not LA terminated, all recurring at follow-up (NLT, n=12). The ECG measures indicated the lowest level of organization in the NLT group for all ablation steps. The highest organization was observed in the LTN group, while the LTR group displayed an intermediate level of organization. Regarding time evolution of ECG measures in dur-PVI and post-PVI recordings, stepwise ablation led to a significant increase in AF organization in most patients (decrease in IF in 68% of patients, increase in AOI in 71% of patients), with no significant differences between the three patient groups. Conclusion: Noninvasive ECG measures could be used to assess pers-AF organization before and during CA, and to identify patients unlikely to benefit from CA. Patterns of temporal evolution in ECG measures of organization are not however associated with ablation outcomes.